Penerapan model pembelajaran kooperatif tipe STAD untuk meningkatkan hasil belajar kimia - Dewi Rostika (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine the increase in learning outcomes of elemental chemistry through the application of the STAD type cooperative learning model. The research subjects were students of class XII IPA 1 SMA Negeri 1 Praya Tengah in the academic year 2017/2018. Research objects are activities and learning outcomes of chemistry. Student learning activity data were collected using observation sheets while student learning outcomes were collected using learning achievement tests. The data obtained were then analyzed descriptively qualitatively. The results of the study were as follows: (1) learning chemistry using the STAD type cooperative learning model could improve learning outcomes of elemental chemistry from cycle I to cycle II and student activity in learning increased from cycle I to cycle II; (2) completeness of learning classically achieved by students in the first cycle was 76.47% with a class average score of 78.32 and in the second cycle increased to 91.18% with a class average score of 86.41. (3) the learning activeness achieved by students classically in the first cycle was 65.45%, increasing in silkus II to 81.82%. Based on the above results by paying attention to the indicators of the implementation of complete learning, it can be concluded that the objectives of this research were achieved and the formulated action hypothesis was acceptable. Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar kimia unsur melalui penerapan model pembelajaran kooperatif tipe STAD. Subjek penelitian adalah siswa kelas XII IPA 1 SMA Negeri 1 Praya Tengah Tahun Pelajaran 2017/2018. Objek penelitian adalah aktivitas dan hasil belajar kimia. Data aktivitas belajar siswa dikumpulkan menggunakan lembar observasi sedangkan hasil belajar siswa dikumpulkan menggunakan tes prestasi belajar. Data yang diperoleh selanjutnya dianalisis secara deskriptif kualitatif. Hasil penelitian adalah sebagai berikut: (1) pembelajaran kimia dengan menggunakan model pembelajaran kooperatif tipe STAD dapat meningkatkan hasil belajar kimia unsur dari siklus I ke siklus II dan aktivitas siswa dalam pembelajaran meningkat dari siklus I ke siklus II; (2) ketuntasan belajar yang dicapai secara klasikal siswa pada siklus I sebesar 76,47% dengan nilai rata-rata kelas 78,32 dan pada siklus II meningkat menjadi 91,18% dengan nilai rata-rata kelas 86,41. (3) keaktifan belajar yang dicapai siswa secara klasikal pada siklus I sebesar 65,45% meningkat pada silkus II menjadi 81,82%. Berdasarkan hasil di atas dengan memperhatikan indikator pelaksanaan pembelajaran tuntas dapat disimpulkan tujuan penelitaian ini tercapai dan hipotesis tindakan yang dirumuskan dapat diterima.